IMPROVING SCIENCE LEARNING OUTCOMES THROUGH THE APPLICATION OF PROJECT-BASED LEARNING MODEL TO FOURTH GRADE STUDENTS OF SD INPRES BANGKALA III MAKASSAR - Ana Vavuu; Waddi Fatimah; Drs. Syamsul Alam (JF Publisher, 2023)
Science subjects require media in teaching. The learning process will not be maximized if the material is only based on textbooks. Therefore, the objectives of this research is to determine the improvement of science learning outcomes through the application of project-based learning model to fourth grade students of SD Inpres Bangkala III Makassar. This type of research is classroom action research which is conducted in a cyclic process with the stages of planning, implementation, observation and reflection. The subjects in this research were the fourth grade students of SD Inpres Bangkala III Makassar consisting of 29 students. The research instruments used in this research were observation sheets, learning outcomes tests and documentation. Data were analyzed by descriptive quantitative. The results of the research indicated that the results of observations of teacher teaching activities in cycle 2 increased to 89.74% with a very good category and the results of observations of student activities increased to 81.81% with a very good category and student learning outcomes reached a minimum completeness criteria score of 82.75%. Therefore, based on the results of this research, it can be concluded that the project-based learning model is able to improve learning outcomes to fourth grade students of SD Inpres Bangkala III Makassar.